How Islamic commercial banks in Indonesia contributing to achieving SDGs-8: Decent work and economic growth? - Fauziah Chairiyati; Evania Herindar; Muhammad Irsyad (Sebelas Maret Business Review, 2024)
The aim is to improve overall well-being and alleviate poverty by achieving the Sustainable Development Goals (SDGs), which are rooted in universal human values and essential rights. In Indonesia, the focus remains on indices of economic sustainability, particularly decent work and economic growth. This study examines the role of Islamic Commercial Banks in Indonesia in achieving SDG-8: Decent Work and Economic Growth from 2016 to 2020. SEM PLS Analysis analyzes Financing, ROA, NPF, and CSR variables to assess their impact on SDG-8 indicators like unemployment, poverty, HDI, and GDP rate. The findings show that while Financing and CSR variables didn't significantly influence SDG-8, the ROA and NPF variables did. A potential reason is that most financing was used for consumption, and CSR programs were only partially aligned with SDG targets. ROA's significance might be due to the correlation between SDGs disclosure and profitability, while NPF's significance might stem from banks promoting sustainable development. The study recommends further attention from practitioners, academics, and regulators.